Discrete-Time Design of Dual Internal Model-Based Repetitive Control Systems - Jalu A. Prakosa; Purwowibowo Purwowibowo; Edi Kurniawan; Sensus Wijonarko; Tatik Maftukhah; Farakka Sari; Enggar B. Pratiwi; Dadang Rustandi (Applied Sciences, 2022)
This paper presents a novel design of discrete-time dual internal model-based repetitive control systems. The design strategy is accomplished by combining general and high-order modified repetitive control schemes for simultaneous tracking repetitive tasks and rejection of uncertain periodic disturbances. The proposed controller is constructed from two different discrete-time internal models, rendering a dual internal model-based repetitive controller (DIMRC). The first internal model is intended to track repetitive commands with a fixed fundamental frequency. Meanwhile, the second internal model is coupled to compensate for an exogenous periodic disturbance with an uncertain frequency. The controller structure, stability conditions, and convergence analysis are discussed in this paper. The performance of the proposed controller is validated through simulation studies showing accurate tracking and excellent disturbance rejection simultaneously.